Electronic tax filing system : Malaysian tax practitioners' technology readiness, acceptance and compliance considerations - Lai, Ming Ling (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2005)
The Inland Revenue Board Malaysia (the lRB) is streamlining the tax administration policies to embrace an electronic tax filing (e-filing) system. With the e-filing system, taxpayers and their representatives can transmit tax returns, payment and information directly to the IRB electronically rather than mailing the paper forms. Experiences of overseas counterparts that have embraced e-filing system have shown that the e-filing system can only work effectively with the assistance and cooperation of tax practitioners. However, at the time of this study, little is known about Malaysian tax practitioners' reactions towards the e-filing system. ln response, this study has, emerged to fill a research void. The objectives of this study are to examine tax practitioners' technology readiness, acceptance and compliance considerations of the e-filing system. A mail survey was used for data collection. Using the systematic sampling method, questionnaires were mailed to 600 tax practitioners throughout Malaysia. Firstly, the Technology Readiness Index (TRI) of Parasuraman and Rockbridge Associates, Inc (1999) was adapted to assess the state of technology readiness amongst tax practitioners. Secondly, an integrated technology acceptance model was developed to examine tax practitioners' acceptance of the e-filing system. The theories underlying the integrated technology acceptance model were generated from the social psychology, information systems, accounting, taxation and marketing literature. Thirdly, this study examined the inherent compliance considerations confronting tax practitioners and also evaluated the importance of five different types of incentives that would motivate tax practitioners to use the e-filing system. Based on TRI, the findings indicated that the respondents were positive towards new technologies. Nonetheless, they were wary about the security of the Internet technology. The respondents were segmented into explorers ( 15% ), pioneers (36% ), sceptics (21 % ), paranoids (26%) and technology laggards (3% ). The structural equation modelling technique was used to test the integrated technology acceptance model. Results showed that behavioural intention (a proxy for technology acceptance) was significantly influenced by the tax practitioner's perceived usefulness, perceived ease of use and perceived insecurity of the e-filing system, as well as perceived behaviour control and social norms. In addition, the survey uncovered the unwillingness of tax practitioners to pay a service fee and their lack of confidence in the electronic administrative capabilities of the IRB. Such factors appeared to discourage the take-up of the e-filing system. At the same time, the survey indicated that the quest for a 'speedy tax refund' ranked the top most important incentive to motivate the use of the e-filing system. Overall, this study provides the needed empirical evidence to the current literature by expanding into a relatively unstudied area of Malaysian tax environment. This study found the applicability of technology acceptance model in Malaysia. The findings have implications and contributions to the tax authonties, and the tax practitioners besides contributing to the theory on modelling user's acceptance of the e-filing system. In addition, this study enhances our understanding on the importance of AICPA's (2001) guiding principles of good tax policy in developing and diffusing the e-filing system in the Malaysian tax environment.